Strategic planning of a community under temporary occupation: a two-phase contingent approach (the case of the Lysychansk community) - Dunayev, Igor; Mordasov, Oleksandr (Theory and Practice of Public Administration, 2026)
The article substantiates a two-phase contingent approach to the strategic planning of a territorial community whose main territory is temporarily occupied and whose population has been forcibly relocated. Drawing on the case of the Lysychansk city territorial community, the authors show that standard local strategic-planning frameworks – designed for full territorial control and access to current statistics – cannot be applied to such communities without deep adaptation. The principal hypothesis is formulated: effective planning is achieved not by adapting a standard single-phase framework but through a distinct two-phase contingent regime in which the object of management and the type of uncertainty differ between the phases, and the transition is activated by an external trigger – de-occupation. Five constructs of the approach and three methodological forks, the traversal of which constitutes this regime, are presented. Using the case, the authors demonstrate that three current strategic goals of Phase A are implemented immediately through annual action plans and budget programmes, while five directions of post-war reconstruction are formalised as a ready but «dormant» Phase B architecture. Drawing on the authors’ own survey of internally displaced persons (February 2024, N = 1415), the auxiliary hypothesis is tested: the intention to return is weakly associated with material conditions and significantly with identity-related and age factors; hence community retention in Phase A should rely on symbolic, informational and targeted instruments rather than material ones alone. A typology is proposed that distinguishes the case of an accessible (de-occupied) community from that of an occupied, relocated community as two different planning regimes. The approach is qualified honestly as a substantiated framework validated on a single case that requires replication to attain the status of a methodology. The results are applicable to dozens of communities in eastern and southern Ukraine with temporarily occupied territory.